Sistemática do gênero Cryptonanus (Didelphimorphia: Didelphidae) baseada em análises moleculares - Fegies, Ana Claudia (2014)
The Cryptonanus genus, in Didelphidae family, is currently constituted by five recognized species restricted to the open vegetation areas of South America: C. agricolai, C. chacoensis, C. guahybae, C. ignitus e C. unduaviensis. Morphological analyses on specimens from Cerrado, Caatinga and Pantanal, indicate the need of taxonomic revision for this group, especially considering its wide range of phenotypic variation and geographic distribution. This study aims to contribute in Cryptonanus species delimitation by evaluating possible patterns of intra and interspecific genetic variation, by the analysis of the phylogenetic relationships from the genetic lineages and their geographic distribution. Combined analysis using mtDNA potentially informative sequences, from cytochrome b (cytb) and subunit I of cytochrome oxidase c (coI) genes, were performed for 51 Cryptonanus specimens, in addition to independent analysis of each marker, 64 specimens for cytb and 54 for coI, sampling a total of 42 localities in South America. Genetic distances were estimated based on a DNA barcode approach. Phylogenetic relationships were retrieved from the results of Maximum Parsimony, Maximum Likelihood and Bayesian Inference methods. The topologies recovered were congruent relative to the position of the genus Cryptonanus as a monophyletic cluster, subdivided in nine clades. Regarding species delimitation, two evolutionary hypotheses were tested: 1- the maintenance of four from five valid taxa (except C. ignitus, since this species was not included in the analyses), based on the characterization of intraspecific genetic variation ranged from 0 to 5,3% (cytb) and from 0 to 5,1% (coI), while interspecific variation ranging from 4,1 to 13,2% (cytb) and from 4,7 to 9,6% (coI), related with genetically structured populations in C. agricolai and C. chacoensis clusters; 2- extended biological diversity, related with the identification of five new species besides the five currently recognized. On this scenario, intraspecific genetic variation ranges from 0 to 2,4% (cytb) and from 0 to 3% (coI), while interespecific variation ranges from 2,1 to 13,2% for cytb and 1,6 to 9,6% for coI. The hypothesis 2 is argued to provide a better picture for species delimitation in Cryptonanus, based on the congruence between geographic structure, intra and interspecific genetic variation ranges and the recovery of reciprocal monophyletic genetic lineages in every phylogenetic analyses.